Å være pårørende når alternativ behandling tas i bruk i “kampen mot kreft” - Rabben, Jannicke; Johannessen, Berit (Nordisk tidsskrift for helseforskning, 2015)
Being relatives when alternative therapies are used in the "fight against cancer"CAM (Complementary and Alternative Medicine) is prevalent among cancer patients. Relatives are central to support and care for the patient but experience challenges and stresses in this role. The purpose of this study was to gain knowledge of how it is experienced to be relative of people with terminal cancer who seeks CAM. Five qualitative semi-structured in-depth interviews of relatives and nine biographies written by relatives were analyzed using systematic text condensation. Results showed that relatives experienced to fight for hope in a given battle, not knowing who you can trust, well-meant pressure from others, putting the sick in the center, a double balance between quality of life and life extension, and mixed feelings in retrospect. The language was characterized by war metaphors. In order to provide better support to relatives it is important that health workers have insight into the paradoxical and ambivalent experience of hope for healing and simultaneously fear of death.